Steinbeck houses in New York City. - Douglas L. Elliman & Co.:::Creator::::::::::::
Real estate photograph of two houses purchased by the Steinbeck's at 175-177, East 78th St. in New York City. John and Gwyn lived in one and rented the other to Nathaniel and Marge Benchley. Original is in the safe.